Low Dose Gamma Irradiation of Trypanosoma evansi Parasites Identifies Molecular Changes That Occur to Repair Radiation Damage and Gene Transcripts That May Be Involved in Establishing Disease in Mice Post-Irradiation - Kangethe, Richard T.; Winger, Eva M.; Settypalli, Tirumala Bharani K.; Datta, Sneha; Wijewardana, Viskam; Lamien, Charles E.; Unger, Hermann; Coetzer, Theresa H.T.; Cattoli, Giovanni; Diallo, Adama (Frontiers in Immunology, 2022)
The protozoan parasite Trypanosoma evansi is responsible for causing Surra in a variety of mammalian hosts and is spread by many vectors over a wide geographical area making it an ideal target for irradiation as a tool to study the initial events that occur during infection. Parasites irradiated at the representative doses 100Gy, 140Gy and 200Gy were used to inoculate BALB/c mice revealing that parasites irradiated at 200Gy were unable to establish disease in all mice. Cytokine analysis of mice inoculated with 200Gy irradiated parasites showed significantly lower levels of interleukins when compared to mice inoculated with non-irradiated and 100Gy irradiated parasites. Irradiation also differentially affected the abundance of gene transcripts in a dose-dependent trend measured at 6- and 20-hours post-irradiation with 234, 325 and 484 gene transcripts affected 6 hours post-irradiation for 100Gy-, 140Gy- and 200Gy-irradiated parasites respectively. At 20 hours post-irradiation, 422, 381 and 457 gene transcripts were affected by irradiation at 100Gy, 140Gy and 200Gy respectively. A gene ontology (GO) term analysis was carried out for the three representative doses at 6 hours and 20 hours post-irradiation revealing different processes occurring at 20 hours when compared to 6 hours for 100Gy irradiation. The top ten most significant processes had a negative Z score. These processes fall in significance at 140Gy and even further at 200Gy, revealing that they were least likely to occur at 200Gy, thus may have been responsible for infection in mice by 100Gy and 140Gy irradiated parasites. When looking at 100Gy irradiated parasites 20 hours post-irradiation processes with a positive Z score, we identified genes that were involved in multiple processes and compared their fold change values at 6 and 20 hours. We present these genes as possibly necessary for repair from irradiation damage at 6 hours, and suggestive of being involved in the establishment of disease in mice at 20 hours post-irradiation. A potential strategy using this information to develop a whole parasite vaccine is also postulated.